2009
DOI: 10.1177/0268580909102910
|View full text |Cite
|
Sign up to set email alerts
|

Family Research from the Life Course Perspective

Abstract: This article presents an argument for overcoming some of the limits of current family research. To start, some major research questions concerning the future challenges of demographic change and its implications for modern welfare states are addressed. The authors propose an agenda for making progress in this field via two interrelated steps. First, they propose an integration of theoretical approaches explaining family dynamics and design a conceptual framework to model couples' and family dynamics as a proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 49 publications
(35 reference statements)
2
53
0
6
Order By: Relevance
“…In terms of individual action, we conceptualize the life course as a complex process of personal welfare production (Huinink and Feldhaus 2009). Creating und sustaining subjective wellbeing implies achieving or maintaining satisfying biographical states and everyday life practices (e.g., having children).…”
Section: The General Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of individual action, we conceptualize the life course as a complex process of personal welfare production (Huinink and Feldhaus 2009). Creating und sustaining subjective wellbeing implies achieving or maintaining satisfying biographical states and everyday life practices (e.g., having children).…”
Section: The General Modelmentioning
confidence: 99%
“…Past experiences affect current fertility decisions, leading to self-selection over time as a consequence of coherence, self-referentiality and path dependence in individual life courses (Huinink and Feldhaus 2009). Little progress has been made in analyzing these phenomena explicitly -that is, not just considered as unobserved heterogeneity one has to account for -in fertility research.…”
Section: Time-related Interdependence Between Past Present and Futurementioning
confidence: 99%
See 1 more Smart Citation
“…One complicated concern is that family roles must often be synchronized across three or more generations at once, even though the synchronization does not go smoothly. However, Huinink and Feldhaus 18 observed that life experiences such as divorce, remarriage, and discontinuities in parents' work and educational trajectories may conflict with the needs of children such as in career building, family and work transitions 18 . The "generation in the middle" may have to make uncomfortable choices when allocating scarce economic and emotional resources.…”
Section: As Shown Inmentioning
confidence: 99%
“…Considering consequences of self-referentiality on the micro-level directs attention to two other related concepts: selection and adaptation (Lesthaeghe 2002;Huinink and Feldhaus 2009). On the one hand, individual intentions, values, and aspirations are a source of selectivity with regard to short-and long-term fertility behavior, but also with regard to other aspects of life such as choosing social environments and social network partners.…”
Section: Complex Dynamics In Fertility Researchmentioning
confidence: 99%